Plastic Waste Test for Makrame - Mutmainah, Siti; Winarno; Ahmad, Asy Syams Elya; Subagio, Agung Ari; Sugianto, Herman (Proceeding of International Joint Conference on UNESA, 2025)
Natural damage due to plastic waste has been felt by humans. The reality that is happening today is that plastic waste has never been used by the community, plastic waste is often thrown away in public places and left alone. The habit of the community in eliminating and destroying plastic waste in general is by burning. Waste burning has a great effect on the surrounding environmental ecosystem, in addition to disturbing the land and sea environment, the burning of plastic waste can affect the depletion of the ozone layer which can ultimately cause global warming for the earth. The purpose of this study is to describe the steps of managing plastic waste as a material for makrame work, and describe the steps of working with plastic waste materials. This research uses a trial or experiment method that is carried out in several stages, starting from designing makrame crafts for two-dimensional and three-dimensional works, determining the makrame technique used, preparing the necessary tools and materials and making makrame from crackle plastic waste. Based on the results of the plastic waste trial, it was concluded that plastic waste can be used as a material for makrame work. The works produced are two-dimensional and three-dimensional, decorative works and functional works.